2021
DOI: 10.1186/s12904-021-00811-5
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ decreased tendency to choose palliative care for patients with advanced dementia between 1999 and 2015

Abstract: Background Physicians’ decision-making for seriously ill patients with advanced dementia is of high importance, especially as the prevalence of dementia is rising rapidly, and includes many challenging ethical, medical and juridical aspects. We assessed the change in this decision-making over 16 years (from 1999 to 2015) and several background factors influencing physicians’ decision. Methods A postal survey including a hypothetical patient-scenari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Providers appear to be skeptical about PC for patients with chronic diseases other than cancer [ 41 ], and many lack the self-confidence to provide such care [ 42 ]. A Finnish study concluded that the low rate of implementation of PC could be associated with unrecognized palliative needs of patients with dementia [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Providers appear to be skeptical about PC for patients with chronic diseases other than cancer [ 41 ], and many lack the self-confidence to provide such care [ 42 ]. A Finnish study concluded that the low rate of implementation of PC could be associated with unrecognized palliative needs of patients with dementia [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, however, a Finnish study, assessing the tendency of physicians to choose PC for patients with AD, using a hypothetical case scenario, reported that PC was chosen less frequently in 2015 than in 1999. The authors suggest that increased reports of legal concerns among physicians in 2015 may partially explain this shift of preferences [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study, conducted in the United Kingdom in 2002/2003, found that people with dementia dying in hospital receive different end-of-life care to those without dementia and are less likely to be referred to palliative care, and to receive palliative medications [ 10 ]. A more recent study also found that Finnish physicians were less likely to choose a palliative care approach for a person with advanced dementia and life-threatening bleeding in 2015 than they were in 1999 [ 11 ]. Studies such as these, have indicated a need for urgent change to improve end-of-life and palliative care for people with dementia, both in Australia [ 12 , 13 ], and internationally [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare professionals are responsible for decisions about how much care patients and family caregivers receive (Haapasalmi et al, 2021). Building knowledge about the cancer patient's family caregivers' needs and expectations is essential.…”
Section: Introductionmentioning
confidence: 99%